Critical thinking skills and sustainability awareness for the implementation of education for sustainable development - Ekamilasari Ekamilasari; Anna Permanasari; Indarini Dwi Pursitasari (Universitas Negeri Yogyakarta, 2021)
Education for Sustainable Development (ESD) is very important for environmental utilization while protecting environmental conditions. Therefore, learning needs to facilitate students to have sustainability awareness and critical thinking skills. This study aimed to analyse critical thinking skills and sustainability awareness among junior high school students through the use of teaching materials in science learning. The samples of the study were 213 students and six teachers of junior high school in Bogor municipality. The data collection technique was a Likert scale questionnaire to determine sustainability awareness, a reasoned multiple-choice critical thinking skill test, and an open questionnaire to explore the need for teaching materials. The results showed that the average sustainability awareness of students was 3.65, which is included in the moderate level. The acquisition of each component of sustainability awareness was sustainability practice awareness (37.95%), behavioural and attitude awareness (70.63%), and emotional awareness (86.92%). The average score of students 'critical thinking skills was 28.68%, which indicated the level of students' critical thinking skills was in a weak category